2014
DOI: 10.1371/journal.pone.0101067
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Skeletal Muscle and Renal Injury to the Lower Limb following Ischemia-Reperfusion Using mPTP Inhibitor NIM-811

Abstract: IntroductionOperation on the infrarenal aorta and large arteries of the lower extremities may cause rhabdomyolysis of the skeletal muscle, which in turn may induce remote kidney injury. NIM-811 (N-metyl-4-isoleucine-cyclosporine) is a mitochondria specific drug, which can prevent ischemic-reperfusion (IR) injury, by inhibiting mitochondrial permeability transition pores (mPTP).ObjectivesOur aim was to reduce damages in the skeletal muscle and the kidney after IR of the lower limb with NIM-811.Materials and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 60 publications
3
29
0
1
Order By: Relevance
“…In young rats, we previously observed that CsA restored skeletal muscle mitochondrial coupling and reduced ROS production during hindlimb IR [23]. Similarly, CsA enhanced mitochondrial recovery after lattissimus dorsi flaps IR in pigs [22] and a nonimmunosuppressive CsA derivative (NIM-811) reduced skeletal muscle injury after IR [24]. Remarkably, the protective effects provided by 10 mg/kg intravenous CsA, given 5 min before reperfusion (reduced muscle infarction, reduced myeloperoxidase activity, and reduced muscle calcium content), were abolished when a mPTP opener atractyloside was injected [22] supporting that CsA is still able to maintain the mPTP in the 'closed' mode, even when provided after ischemia.…”
Section: Effects Of Cyclosporinementioning
confidence: 88%
See 1 more Smart Citation
“…In young rats, we previously observed that CsA restored skeletal muscle mitochondrial coupling and reduced ROS production during hindlimb IR [23]. Similarly, CsA enhanced mitochondrial recovery after lattissimus dorsi flaps IR in pigs [22] and a nonimmunosuppressive CsA derivative (NIM-811) reduced skeletal muscle injury after IR [24]. Remarkably, the protective effects provided by 10 mg/kg intravenous CsA, given 5 min before reperfusion (reduced muscle infarction, reduced myeloperoxidase activity, and reduced muscle calcium content), were abolished when a mPTP opener atractyloside was injected [22] supporting that CsA is still able to maintain the mPTP in the 'closed' mode, even when provided after ischemia.…”
Section: Effects Of Cyclosporinementioning
confidence: 88%
“…CsA inhibits mitochondrial transition pore (mPTP) opening and therefore antagonizes apoptosis. CsA given at the onset of reperfusion was shown to protect myocardial [21] and skeletal muscles [22][23][24] from IR-induced injury in adult patients and rats, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increase in local injury, necrosis and rhabdomyolysis, as well as of their systemic repercussions. The metabolics and pro-inflammatory cytokines originating from muscular injury may induce Systemic Inflammatory Response Syndrome, and may affect distant organs, such as kidneys, lung and gastrointestinal tract -multiple organ dysfunction 13 . Among these organs, the lung was the one analyzed in the present study.…”
Section: ■ Discussionmentioning
confidence: 99%
“…They reported that muscle mitochondrial viability proved to be significantly higher and renal function parameters significantly better in the treatment group (18).…”
Section: Discussionmentioning
confidence: 98%